1D Structure Sodium Coordination Anion based on [5‐(Dinitromethylene)‐4, 5‐dihydro‐1H‐tetrazole]: Syntheses, Structures, and Thermal Behavior. Issue 18 (17th August 2016) - Wu, Le; Zhang, Jian‐Guo; Wu, Jin‐Ting; Yin, Xin; He, Piao
Abstract: The ten‐coordinate complex, (HATr)[Na(DNMz)]· H2 O (1 ) was synthesized by reaction of 5‐(dinitromethylene)‐4, 5‐dihydro‐1 H ‐tetrazole (DNMz), sodium hydroxide, and 3‐hydrazinium‐4‐amino‐1, 2, 4‐1 H ‐triazolium dichloride (HATr) in aqueous solution and characterized by various physico‐chemical techniques. Complex 1 is an energetic material with a nitrogen content of 51.2 % and a decomposition temperature of 128.9 °C. The molecular structure of complex 1 crystallizes in the monoclinic system with P 2(1)/ c group and shows an infinite 1D chain structure. The heat of formation was determined as –122.27 kJ· mol –1 by using bomb calorimetry. In addition, the kinetic parameters were studied by Kissinger's and Ozawa‐Doyle's methods. Abstract :